Sustainability of corrosion-induced degradation of marine engineering structures: A bibliometric analysis based on CiteSpace and VOSviewer (1972-2026) - Zihan Yang; Guangda Yu; Chengyong Li; Bingxuan Zhao; Yansong Liu; Guoqiang Tang; Weihang Yu; Qianhua Liu; Luning Liu; Yu Sun; Yuxin Shi; Zining Li; et al. (Marine Environmental Research, 2026)

Temperature-driven metagenomics reveals reshaping of microbial communities and nitrogen cycling functions and their potential impacts on Chinese sturgeon host health - Jiachen Zhou; Huifeng Dang; Ye Zhang; Luning Li; Jianan Xu; Houyong Fan; Yueping Zheng; Dan Xu (Aquaculture, 2026)

Integrated multi-omics and physiological analyses reveal mechanism of enhanced gellan gum biosynthesis in an ARTP-induced Sphingomonas paucimobilis mutant - Ling Sun; Shiyi Chen; Yazhen Wang; Lei Sun; Zejian Wang; Yong Zhou; Ali Mohsin; Suyang Li; Luning Zhao; Afira Nayab; Wenjing Sun (Food Microbiology, 2026)

A hybrid assembly mechanism employs nonreducing polyketide synthase-like logic for partially reduced polyketide formation - Xianyan Zhang; Chuanteng Ma; Ziguang Deng; Xingtao Ren; Kaijin Zhang; Wenxue Wang; Luning Zhou; Yongchun Zhu; Guojian Zhang; Qian Che; Tianjiao Zhu; Hongan Long; et al. (Marine Life Science & Technology, 2026)
Fungal iterative type I polyketide synthases (iPKSs) are commonly classified into nonreducing (NR-), partially reducing (PR-), and highly reducing (HR-) polyketide synthases based on their assembly mechanisms and domain structures. These iPKSs have been considered functionally and evolutionarily distinct, characterized by clear boundaries. However, emerging genomic analyses suggest that the diversity of iPKSs in fungi is far from fully understood. Here, we describe the discovery and characterization of PbPKS1 from a marine-derived fungus Penicillium brocae HDN12-143, which exhibits an atypical domain organization arranged as KR-KS-AT-PT-ACP 1 -ACP 2 -CMeT-TE. Heterologous expression of PbPKS1 resulted in the production of two monohydroxybenzoic acids and two pyrones. In vivo and in vitro characterizations demonstrated that PbPKS1 has the capability to synthesize Cα-methylated partially reducing polyketides, yet involved a NR-PKS-like assembly mechanism, featuring a product template (PT) domain for aldol cyclization and a C-terminal thioesterase (TE) domain for product release. Phylogenetic analysis suggests that PbPKS1 belongs to a non-canonical PR-PKS (nPR-PKS) family, which is a minor grouping across the fungal kingdom, and possibly evolved from an NR-PKS through gene recombination. The discovery of nPR-PKS not only expands the diversity of iPKSs but also provides new insights into the evolutionary development of fungal iPKSs.

Novel antifungal talaroenamine L with unusual leptosphaeronyl moiety from marine-derived Talaromyces sp. HDN17-428 via HDACi elicitation - Komal Anjum; Luning Zhou; Khizar Hayyat; Xiaofei Huang; Jiaxiang Wang; Guojian Zhang; Tianjiao Zhu; Qian Che; Dehai Li (Natural Product Research, 2025)

Differences in Mesozoic–Cenozoic Structural Deformation Between the Northern and Southern Parts of the East China Sea Shelf Basin and Their Dynamic Mechanisms - Chuansheng Yang; Junlan Song; Yanqiu Yang; Luning Shang; Jing Liao; Yamei Zhou (Journal of Marine Science and Engineering, 2025)
The East China Sea Shelf Basin (ECSSB) and its adjacent areas, as key regions of the ocean–continent transition zone, have been affected by multiple complex plate collisions, subduction, and back-arc tension since the Mesozoic Era. The structural deformation provides a large amount of geological information on the ocean–continent transition zone. There are significant spatiotemporal differences in the structural deformation within the basin. However, the research remains insufficient and understanding is inconsistent, especially regarding the systematic study of the differences and dynamic mechanisms of north–south structural deformation, which is relatively lacking. This study is based on two-dimensional multi-channel deep reflection seismic profiles spanning the southern and northern basin. Through an integrated re-analysis of gravity, magnetic, and OBS data, the deformation characteristics and processes of the Meso-Cenozoic structures in the basin are analyzed. The differences in structural deformation between the southern and northern basin are summarized, and the controlling effects of deep crust–mantle activity and the influencing factors of shallow structural deformation are explored. Based on deep reflection seismic profiles, the structural deformation characteristics of the Yushan–Kume fault are revealed for the first time, and it is proposed that NW faults, represented by the Yushan–Kume fault, have important tuning effects on the north–south structural differential deformation in the ECSSB. The thermal subsidence of the lithosphere is the direct cause of the development of the Mesozoic ECSSB, while the subduction of the Paleo-Pacific plate is one of the important factors contributing to it. The combined effect of the two has led to significant differences between the northern and southern Mesozoic basin. During the Cenozoic Era, the alternating subduction and changes in the direction of subduction of the Pacific Plate led to spatiotemporal differences in structural deformation within the ECSSB. The development of NW faults was a key factor in the differences in structural deformation between the northern and southern basin. The study of structural deformation differences in the ECSSB not only deepens our understanding of the tectonic evolution in the East Asian continental margin region, but also has important significance for the exploration and evaluation of deep hydrocarbon resources in the ECSSB.

Biocontrol efficiency and multiple mechanisms of Bacillus velezensis BV07 against postharvest green mold on citrus fruit - Chenyang Zhu; Juanying Huang; Mengyue Wu; GuangHao Li; Xiaoshuang Xia; Luning Zhao; Mahmoud Salah; Xinghua Zhou; Yun Wang (Postharvest Biology and Technology, 2025)

Stronger together: a cross-SIG perspective on improving drug development - Luke Fostvedt; Jiawei Zhou; Anna G. Kondic; Ioannis P. Androulakis; Tongli Zhang; Meghan Pryor; Luning Zhuang; Jeroen Elassaiss-Schaap; Phyllis Chan; Helen Moore; Sean N. Avedissian; Jeremy Tigh; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

New cyclic dipeptide discovered from deep-sea derived Aspergillus sp. HDN20-1401 - Komal Anjum; Xiaofei Huang; Luning Zhou; Tianjiao Zhu; Qian Che; Guojian Zhang; Dehai Li (Natural Product Research, 2024)

New Antibacterial Dihydropyrones Induced by Co-Culture of Penicillium crustosum PRB-2 and Penicillium citrinum HDN11-186 - Guihong Yu; Luning Zhou; Guangwei Wu; Dehai Li (Journal of Ocean University of China, 2024)

Induced seismicity in the Changning salt mining zone, China, could be driven by the pore-pressure diffusion - Haozhe Yang; Rumeng Guo; Guang Zhai; Jiangcun Zhou; Kun Dai; Yong Zheng; Luning Li; Heping Sun (Tectonophysics, 2024)

Grey-matter volume as a potential feature for the classification of Alzheimer’s disease and mild cognitive impairment: an exploratory study - Yane Guo; Zengqiang Zhang; Bo Zhou; Pan Wang; Hongxiang Yao; Minshao Yuan; Ningyu An; Haitao Dai; Luning Wang; Xi Zhang; Yong Liu (Neuroscience Bulletin, 2014)